Renal transplantation as a renal replacement therapy in patients with renal cell cancer (RCC) - Borkowski, Andrzej (Contemporary Oncology/Współczesna Onkologia, 2005)
Easy access to dialysis, due to development of hemodialysis centers, unable renal replacement therapy after nephrectomy in patients with bilateral RCC or RCC involving solitary functional kidney. In some medium size tumors or tumors in unfavorable anatomical locations, choice between nephron sparing surgery (NSS) or nephrectomy with renal replacement therapy, may be not obvious and easy, therefore should be discussed in details with a patient. In a patients with a small accidentally diagnosed tumor, nephrectomy might be followed by immediate renal transplantation but in a case of Wilms tumors or big symptomatic RCC, especially with capsular involvement, renal transplantation should be postponed for a period of at least 2 years. A tumor in a graft is not an unusual finding, both as a new development ( de novo ), or as a tumor unrecognized before transplantation. In this aspect careful examinations of the donors, especially related donors in a familial forms of RCC in patients with VHL is mandatory. A very strict surveillance after transplantation is also very important. This should facilitate recognition of the tumors undiagnosed in the graft before transplantation or a new tumors development accelerated by immunosupression. Nowaday, NSS or percutaneous cryoablation or thermoablation can be offered to these patients.